Pewarisan Karakter Fenotip Ayam Hasil Persilangan Ayam Pelung dengan Ayam Cemani - Setiadi Daryono, Budi; Roosdianto, Iwan; Tri Sakti Saragih, Hendry (Jurnal Veteriner; Vol 11 No 4 (2010))
The germ plasm variability of Indonesian local chicken is well known and one species which known as“ayam Pelung” originated from West Java is famous for its meat. The present study aimed to observed thephenotype characters i.e. fur color and body weight in a crossbreed hybrids of Pelung and Cemani chickenas a potential meat type breed. Firstly, the breeding between Pelung (one male) and Cemani (4 Females)was performed in semi intensive cage. Secondly, experiment were undertaken using 4 groups of DOC (eachcontain 5 males DOC) : 1) DOC of broiler Cobb 500 vs broiler Cobb 500 ; 2) DOC of Pelung vs Pelung ; 3)DOC of Pelung vs Cemani ; and 4) DOC of Cemani vs Pelung. The animals were kept for 7 weeks (49 days)every week the animals body weight and fur color were recorded. The result showed that there weredifferences in the phenotype characters of between the different crossbreeds. The fur of 5 F1 (femaleCemani vs male Cemani) was black with average body weight 532 ± 39.294 g at week 7. Whilst the fur colorof majority (4/5) F1 (female Pelung vs male Cemani) was black with brown dots with average body weight570 ± 14.445 g at week 7. When Pelung was cross within the same species their F1 fur color was blendedbetween black, brown and whitish with average body weight 652 ± 33.846 g at week 7. It is concluded that,the parent stock in this case the Cemani play a major role in fur color character whereas there ware nodifferences in the body weight at the F1 between the two different parent stock (ie. Pelung, Cemani).
Keywords: Germ plasm, Cemani chick, Pelung chick, phenotype characters.